Mapping the fine structure of cortical activity with different micro-ECoG electrode array geometries. (16th August 2017) - Wang, Xi; Gkogkidis, C Alexis; Iljina, Olga; Fiederer, Lukas D J; Henle, Christian; Mader, Irina; Kaminsky, Jan; Stieglitz, Thomas; Gierthmuehlen, Mortimer; Ball, Tonio
Abstract: Objective . Innovations in micro-electrocorticography ( µ ECoG) electrode array manufacturing now allow for intricate designs with smaller contact diameters and/or pitch (i.e. inter-contact distance) down to the sub-mm range. The aims of the present study were: (i) to investigate whether frequency ranges up to 400 Hz can be reproducibly observed in µ ECoG recordings and (ii) to examine how differences in topographical substructure between these frequency bands and electrode array geometries can be quantified. We also investigated, for the first time, the influence of blood vessels on signal properties and assessed the influence of cortical vasculature on topographic mapping. Approach . The present study employed two µ ECoG electrode arrays with different contact diameters and inter-contact distances, which were used to characterize neural activity from the somatosensory cortex of minipigs in a broad frequency range up to 400 Hz. The analysed neural data were recorded in acute experiments under anaesthesia during peripheral electrical stimulation. Main results . We observed that µ ECoG recordings reliably revealed multi-focal cortical somatosensory response patterns, in which response peaks were often less than 1 cm apart and would thus not have been resolvable with conventional ECoG. The response patterns differed by stimulation site and intensity, they were distinct for different frequency bands, and the results of functional mapping proved independent of cortical vascular. Our analysis of different frequency bands exhibited differences in the number of activation peaks in topographical substructures. Notably, signal strength and signal-to-noise ratios differed between the two electrode arrays, possibly due to their different sensitivity for variations in spatial patterns and signal strengths. Significance . Our findings that the geometry of µ ECoG electrode arrays can strongly influence their recording performance can help to make informed decisions that maybe important in number of clinical contexts, including high-resolution brain mapping, advanced epilepsy diagnostics or brain–machine interfacing.